Increased compositional heterogeneity of mass‐flowering orchard crops does not promote wild bee abundance in orchards. (26th August 2021) - Pisman, Matti; Eeraerts, Maxime; Ariza, Daniel; Smagghe, Guy; Meeus, Ivan
Abstract: Due to increasing difficulties to maintain semi‐natural habitat within agricultural landscapes, management of the agricultural matrix may provide a more realistic approach to support farmland biodiversity and associated ecosystem services. We hypothesize that orchard compositional heterogeneity (OCH), that is, different mass‐flowering crops with sequential blooming periods, may support pollinators through continuous abundance of floral resources. We assessed whether increased OCH at the landscape level had a positive effect on wild bee abundances in sweet cherry and apple orchards during bloom. We monitored 15 sweet cherry and 14 apple orchards in Flanders, Belgium, situated along a gradient of OCH. We performed pollinator surveys during bloom to measure wild bee and honey bee abundance and monitored fruit development to assess fruit set and quality. We found no positive effect of OCH on wild pollinator abundance in our study system. Solitary bees showed contrasting responses between crops. Bumble bees showed no response. Wild pollinator abundance had a positive effect on sweet cherry fruit set and apple seed set. Our results imply that increasing crop compositional heterogeneity solely in terms of orchard crops with a limited difference in bloom phenology may prove to be insufficient to support pollinators. We confirm the importance of wild pollinators for pollination services in horticulture.